Valorization Of Industrial Ash Waste As Eco-Friendly Binder For Pavement Applications: Experimental Study On Strength And Permeability Properties - Ruben Alexis; Camacho Huereca (Civil Engineering Science and Technology, 2025)
As the construction industry faces increasing pressure to reduce its environmental footprint, the use of industrial byproducts as alternative construction materials presents a promising strategy for promoting sustainability. This study investigates the potential valorization of industrial ash waste, particularly fly ash and steel slag, as an eco-friendly binder in permeable pavement applications. The main objective is to engineer a sustainable binder mix that aligns with circular economy principles while maintaining structural and hydraulic performance, particularly in tropical climate conditions. A series of experimental tests was conducted on various ash-based binder formulations to evaluate compressive strength, permeability rate, and durability under simulated tropical environmental exposure. Complementary microstructural analyses using scanning electron microscopy (SEM) and X-ray diffraction (XRD) were also performed to explore the internal bonding characteristics and hydration behavior. The results revealed that specific combinations of fly ash and steel slag achieved compressive strength values comparable to conventional cement-based binders, while exhibiting significantly higher water permeability, an essential feature for stormwater management in urban areas. Moreover, the binder demonstrated good resistance to moisture-induced degradation. These findings suggest that industrial ash waste can be effectively transformed into high-performance, low-impact materials for green infrastructure. This research contributes to both material innovation and sustainable engineering practices, offering a viable solution for environmentally responsible pavement design in developing countries with tropical climates.